Comparing tests of autoregressive versus moving average errors in regression models using Bahadur's asymptotic relative efficiency - C. R. MacKenzie; Michael MacAleer (Osaka University, Institute of Social and Economic Research (ISER), 2001)
The purpose of this paper is to use Bahadur's asymptotic relative efficiency measure to compare the performance of various tests of autoregressive (AR) versus moving average (MA) error processes in regression models. Tests to be examined include non-nested procedures of the models against each other, and classical procedures based upon testing both the AR and MA error processes against the more general autoregressive-moving average model.
Keywords: 330; autoregressive model; Bahadur efficiency; inappropriate alteratives; Lagrange multiplier test; moving average model; separate (non-nested) tests; Schätztheorie; Theorie; Statistischer Fehler